Penggunaan Media Pembelajaran Bahasa Indonesia Menggunakan Smart App Creator - Intan Rossa; Didah Nurhamidah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research was conducted to see the effectiveness of using the Smart App Creator learning media in learning material elements of folk poetry at SMP Negeri 153 Jakarta. This research is a research that uses a qualitative descriptive method. The research population was all students of class VII with a total of 36 students. The data collection technique used was a questionnaire using a questionnaire research instrument with a total of 10 statements filled out by students through the Google Form. Based on research data and discussion results, it shows that the Smart App Creator learning media is effectively used in learning material elements of folk poetry for class VII at SMP Negeri 153 Jakarta. However, some respondents still considered doubtful and disagreed, therefore the teacher had to develop various forms of variations on Smart App Creator learning media, and needed to test comparisons between the use of Smart App Creator learning media and using other digital learning media so that teachers can use learning media in teaching activities to be more diverse.